Activation of the Plasmodium Egress Effector Subtilisin-Like Protease 1 Is Mediated by Plasmepsin X Destruction of the Prodomain - Sumit Mukherjee; Armiyaw S. Nasamu; Kelly C. Rubiano; Daniel E. Goldberg (mBio, 2023)
ABSTRACT Following each round of replication, daughter merozoites of the malaria parasite Plasmodium falciparum escape (egress) from the infected host red blood cell (RBC) by rupturing the parasitophorous vacuole membrane (PVM) and the RBC membrane (RBCM). A proteolytic cascade orchestrated by a parasite serine protease, subtilisin-like protease 1 (SUB1), regulates the membrane breakdown. SUB1 activation involves primary autoprocessing of the 82-kDa zymogen to a 54-kDa (p54) intermediate that remains bound to its inhibitory propiece (p31) postcleavage. A second processing step converts p54 to the terminal 47-kDa (p47) form of SUB1. Although the aspartic protease plasmepsin X (PM X) has been implicated in the activation of SUB1, the mechanism remains unknown. Here, we show that upon knockdown of PM X, the inhibitory p31-p54 complex of SUB1 accumulates in the parasites. Using recombinant PM X and SUB1, we show that PM X can directly cleave both p31 and p54. We have mapped the cleavage sites on recombinant p31. Furthermore, we demonstrate that the conversion of p54 to p47 can be effected by cleavage at either SUB1 or PM X cleavage sites that are adjacent to one another. Importantly, once the p31 is removed, p54 is fully functional inside the parasites, suggesting that the conversion to p47 is dispensable for SUB1 activity. Relief of propiece inhibition via a heterologous protease is a novel mechanism for subtilisin activation. IMPORTANCE Malaria parasites replicate inside a parasitophorous vacuole within the host red blood cells. The exit of mature progeny from the infected host cells is essential for further dissemination. Parasite exit is a highly regulated, explosive process that involves membrane breakdown. To do this, the parasite utilizes a serine protease called SUB1 that proteolytically activates various effector proteins. SUB1 activity is dependent on an upstream protease called PM X, although the mechanism was unknown. Here, we describe the molecular basis for PM X-mediated SUB1 activation. PM X proteolytically degrades the inhibitory segment of SUB1, thereby activating it. The involvement of a heterologous protease is a novel mechanism for subtilisin activation.